Public Perceptions of Digital Banking Service Quality and the Relationship on Customer Satisfaction in Medan City, Indonesia - Sianturi, Charles Makmur; Gultom, Anthasia Grace br (Manunggal Halim Jaya, 2026)
This study aims to empirically examine the effect of the quality of digital banking services on customer satisfaction in Medan City. This research employs a quantitative approach, with customer satisfaction as the dependent variable and the dimensions of service quality—namely time efficiency, convenience, high accuracy, security, and reliability—as the independent variables. The sampling method used is non-probability sampling, with the sample size determined using a quota sampling technique. Data were measured using a Likert scale and collected through the distribution of questionnaires. The analysis method used is multiple regression analysis, accompanied by classical assumption testing using SPSS version 26. The results of the analysis show that all independent variables have positive and significant regression coefficients. Therefore, it can be concluded that the independent variables—time efficiency, convenience, high accuracy, security, and reliability—positively influence customer satisfaction, with the convenience variable having the strongest effect among them.